A ROTINA COM BEBÊS E CRIANÇAS BEM PEQUENAS NOS CENTROS MUNICIPAIS DE EDUCAÇÃO INFANTIL DE GUARAPUAVA-PR: INVISIBILIDADES E SILENCIAMENTOS - NASCIMENTO, EDANIELE CRISTINE MACHADO DO (2015)
The pedagogic actions organization in different levels of teaching is an important factor to the quality of developed work and it must be flexible and planned based on each context. Thus, the organization routine babies with of childhood education institutions should consider how specific characteristics of children in this age range, conceiving the baby as a competent social person having rights as breeder child together adults and other children, a person who has knowledge, culture and identity. In this sense, the general objective of this study was to recognize and to enquire about the practice regarding babies’ daily routine in Children Education Municipal Center in the city Guarapuava/PR. The specific objectives were to understand conceptions, speeches and teachers and managers’ opinion in nurseries about their work taking care babies; to interpret babies’ reactions on their daily routine and to enquire about the relation between adults and children. Based on a qualitative-interpretative study characterized by the case study data were collected by observations of the daily routine in three public children educational institutions in the city, by recordings on field diary and interviews with professionals who works in this context. On an interdisciplinary dialogue we used main theoretical references contributions from education, children sociology and anthropology studies understanding the childhood as a social, historical and cultural category. We dialogued specially Barbosa (2006), Coutinho (2009), Kuhlmann Jr. (2010), Rosemberg (1986), Serres (2003), Stambak (2011), Gottlieb (2009), Schmitt (2011) and Tristão (2005), and other. Analysis uncovered into researched institutions that the daily routine, children and adults’ activities and time and spatial organization are extern and inflexible. The routine was planned depending on CMEIs infrastructure and schedule especially regarding cooking, cleaning and professionals’ activities considering babies’ specific nature and singularity. Then this study uncovered that the daily routine is organized and planned based on adulthood logic and not on children’s needs. The emerging context points to the importance of resizing prevailing practices into educational institutions for zero-three-children considering babies as active people in their development and respecting them as they are.